(untitled) (Journal of Nepal Geological Society, 2018)
This study detected 897 dormant landslides of deep-seated type in the upper course of the Sun Kosi Watershed. It also shows geology and slope gradient that are prone to cause deep-seated landslides in the Great Himalaya and Midland zones. The dormant landslides are predominantly distributed in geological areas of the Augen Gneiss, Benighat Slate, Robang Phyllite and the Kuncha Phyllite, considering both landslide area ratio and site number. Landslides of deep-seated type are also found prone to develop on dip-slope. Occurrence of landslides usually increases over 20 degrees of slope angle for each geological type, though the number of landslides in the phyllite area increases below 20 degrees. It is very clear that landslides in phyllite area are prone to occur from relatively lower slope angles compared to those occurring in quartzite, gneiss and the Sermathang Formation. Nepal Gorkha Earthquake 2015 caused 1804 landslides in this study area. Most of the earthquake-induced landslides are of shallow types that occurred just below break of slope, showing a shoulder shaped profile along the deep gorge. They are predominantly distributed on steep slopes in the geological areas of slate, gneiss and dolomite. None of the dormant landslides of large scale was activated by the earthquake.